ANALYSIS OF COMMUNITY PARTICIPATION IN DEVELOPMENT PLANNING IN KALIJAGA VILLAGE, HARJAMUKTI SUB-DISTRICT, CIREBON CITY - Muhammad Faisal; Dahyar Daraba (Universitas Padjadjaran, 2023)
This study aims to determine and analyze community participation in the development planning process in Kalijaga Village, Harjamukti District, Cirebon City, West Java Province. The approach used is qualitative. Data sources are the Head of Cirebon City Regional Development Planning Agency, Harjamukti Sub-District Head, Kalijaga Urban Village Chief, Hamlet Heads, and Community Representatives. Data collection techniques using semi-structured interviews, observation, and documentation. Furthermore, the data were analyzed using stage 3 flow, namely data reduction, data display and conclusion drawing or verification. The study’s results explained that community participation in the development planning process in Kalijaga Village, Harjamukti Sub-District, Cirebon City, was relatively low. Community limitations influence the low community participation in the development planning process in understanding development planning. There is a pessimistic attitude of the community towards the development planning process because their proposals are not accommodated in the higher process, the limited number of officials and development cadres in charge of communicating information about development planning to the community, and the implementation time of development planning is relatively short, so it is not balanced with the material that must be discussed and decided.